The Effectiveness of Elsa Speak Application to Improve Pronunciation Ability - Rinaepi; Henni Rosa Triwardani; Raysal Nur Azi (Universitas Islam Al-Ihya Kuningan, 2022)
English pronunciation is one of essential aspect to learn English as a second language. It becomes the reason why this research conducted. The existence of ELSA application as a media is considered to be something new that able to make learners more interested to learn Engish. The use of this media aims to take advantage of technological advances in an effort to make it easier for students to improve their pronunciation skills which will then be very useful for students when facing the world of international work. The researcher uses experimental research in which Elsa Speak is the independent variable and pronunciation is the dependent variable. By using random sampling technique the researcher took sample of 11 students from a total population 37 students of class XI SMK Taruna Bhakti Kadugede and data collection techniques is observation, test, and documentation. The result showed that the use of Elsa Speak can improve students’ learning motivation by 25.45%, and the results statistical analysis of the Pre-Test and Post-Test show that using Elsa Speak can improve students' pronunciation ability by 17 %. The conclusion of this research is that Elsa Speak is able to improve the pronunciation ability of the XI grade students of SMK Taruna Bhakti Kadugede.